Review of the AfCFTA registration and rules of origin certification process: A case study of Ghana - Muhammed Abdulai; Wilfred Essuman; Apraku Anane-Appiah; Anthony Yeboah; Naazia Ibrahim; Eric Osman; George Amoah; Prachi Agarwal; Derrick Abudu (ODI, 2024)
The African Continental Free Trade Area (AfCFTA) is a game-changer for businesses across Africa, promising reduced trade barriers and increased market access. This report examines the AfCFTA Rules of Origin (RoO) certification process in Ghana, a critical factor in determining which products qualify for preferential tariffs under the agreement. Nearly two years after the AfCFTA's implementation, this study utilises empirical data collection and public-private sector dialogue to assess Ghana's current RoO certification process, compare it against AfCFTA guidelines, assess businesses' experiences and explore gender and climate change considerations. The study involved interviews with key stakeholders, surveys of businesses and case studies of firms using different certification processes. Findings indicate that Ghana's process, while generally aligned with AfCFTA guidelines, is more complex than necessary. Businesses often struggle to understand and meet RoO criteria, highlighting the need for simplification and greater support.
Keywords: 330; Economic transformation; Economic growth; Ghana; Africa; Trade & investment